Delineation of landslide susceptible zones using Frequency Ratio (FR) and Shannon Entropy (SE) models in northern Rif, Morocco - Abderrazzak Es-smairi; Brahim Elmoutchou; Riyaz Ahmad Mir; Abdelouahed El Ouazani Touhami; Mustapha Namous (Geosystems and Geoenvironment, 2023)
This study describes the findings of landslide susceptibility modelling and hazard analysis in the coastline Mediterranean between Tetouan-Bou Ahmed and its hinterlands North Morocco. The study was carried out using Frequency Ratio (FR) and Shannon Entropy (SE) models with the aid of GIS tools and remote sensing data sources supported by extensive field surveys. A methodology was developed for modelling and identifying the landslide susceptible zones and for generating an updated landslide inventory map to delineate the most sensitive landslide prone areas as well as to predict and reduce their impacts. For building these models, a total of 905 landslide incidences and eleven main landslide causative factors were used based on multi-collinearity diagnosis test. The validation of the model results showed good prediction ability (>76%) for both the models. However, the accuracy prediction indicated that the FR is about 3% more precise than SE model in landslide susceptibility delineation. Furthermore, more than 60% of the area was found as high risk zone that is predicted highly susceptible to the landsliding hazards under suitable triggering factors. The findings of this study constitutes a major and suitable database for local and national authorities for providing stratigies for landslide hazard mitigation and making better policies for sustainable development in the region. Sustainable adaptive solutions and measures are required to prevent the stability of this mountainous region which is under the impact of wide anthropogenic activities for developmental purposes.